Haploidentical haematopoietic stem cell transplantation for TP53‐mutated acute myeloid leukaemia. (8th November 2022) - Huang, Ting; Xu, Lanping; Zhang, Xiaohui; Chang, Yingjun; Mo, Xiaodong; Sun, Yuqian; Huang, Xiaojun; Wang, Yu
Summary: Acute myeloid leukaemia (AML) patients with tumour protein p53 ( TP53 ) mutations are often resistant to chemotherapy and have worse clinical outcomes than patients without TP53 mutations. In this study, we compared clinical outcomes of patients with AML with and without TP53 mutations who underwent haploidentical haematopoietic stem cell transplantation (haplo‐HSCT). For the TP53 ‐mutation group and TP53 wild‐type group, the 2‐year cumulative incidence of relapse (CIR) was (39.0% vs. 21.2% respectively, p = 0.088), the 2‐year non‐relapse mortality (NRM) rate was (3.2% vs. 8.4% respectively, p = 0.370), the 2‐year leukaemia‐free survival (LFS) was (57.7% vs. 71.3% respectively, p = 0.205), the 2‐year overall survival (OS) rate was (69.9% vs. 81.3% respectively, p = 0.317), the 100‐day cumulative incidence of Grade II–IV acute graft‐versus‐host disease (GvHD) was (6.5% vs. 20.7% respectively, p = 0.074), the 2‐year cumulative incidence of chronic GvHD was (52.3% vs. 53.1% respectively, p = 0.493) and the 2‐year GvHD‐free/relapse‐free survival (GRFS) was (57.7% vs. 69.6% respectively, p = 0.347). Our data showed that there were no significant differences in 2‐year clinical outcomes between the two groups. Multivariable analysis showed TP53 mutations had no significant impact on CIR, NRM, OS, GvHD, LFS or GRFS. Our findings suggest that patients with AML with TP53 mutations may at least partially benefit from haplo‐HSCT. Haplo‐HSCT might be the recommended treatment for such patients.